"Incorporating a Gym Facility in a Lifestyle Medicine Practice for Patients with Diabetes Mellitus". Issue 3 (May 2023) - Nadolsky, Karl; Baraki, Austin; Nadolsky, Spencer
Incorporating a gym or fitness facility into a lifestyle-focused clinic is potentially one of the most critical facets of the patient-focused care, especially for those with obesity, cardiometabolic disease, and all types of diabetes mellitus. The evidence for prioritizing physical activity and exercise as medicine is well-researched and universally recommended as first-line therapy plus prevention of many chronic disease states. Having a fitness center on-site as part of any clinic could improve patient utilization, reduce barrier to entry, and decrease hesitation to engage in exercise like resistance training. While the conceptualization may seem simple, the pragmatic application and implementation takes proper planning. Developing such a gym will depend upon gym size preference, program development, cost, and available personnel. Thought needs to be put into deciding which type of exercise and ancillary equipment, ranging from aerobic or resistance machines to free weights, will be included and in what format. Fee and payment options should be carefully considered to assure the budget works financially for both the clinic and patient population. Finally, graphic examples of clinical gyms are described to convey the potential reality of such an optimal setting.